Experiences Of Female Workers: Protagonists Of (A Lack Of) Care, In Ciudad Juarez, Chihuahua, Mexico - Robles Ortega, Rosalba (Advances in Social Sciences Research Journal, 2016)
The paid work of women in the Maquiladora[1] Export Industry, in Ciudad Juarez, Chihuahua, Mexico, has been a cause of serious physical and emotional distress that they suffer. This has fostered in the women – as working women – a lack of care towards those they commonly cared for – children, grandchildren, parents – as well as the omission of self-care. Having to perform double and triple working days on a daily basis, has led them to develop not only physical-biological-bodily pain, but also guilt and conflicting emotions as a result of not meeting their socially assigned role based on the sexual division of labor, the care of children, and therefore, having to delegate this responsibility. The entry of women into the production market, added to activities that multiplied, while working time was extended, thereby generating a visible deterioration in their quality of life, and in that of those who they looked after. Hence the importance of addressing this problem and being able to detect what have been and/or what are the physical and emotional costs that these women navigate, and that hinder the care that they owe themselves. [1] A maquiladora is a factory operated in Mexico under preferential tariff programs established by the U.S. and Mexican governments.